Defining and Classifying Corporate Social Costs: An Initiative to Enrich the Thought of Accounting for CSR - Younis A. Battal Saleh (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: This desk research aims to provide a clear and precise definition of the term "corporate social costs (CSCs)" from the perspective of accountants and to determine a set of standards by which CSCs may be separately identified from corporate economic cost (CECs).  Method: Rational thinking and logical reasoning are frequently used in theoretical studies that seek to advance and strengthen the theoretical framework of any major in the social sciences, including accounting and economics.  Therefore, in order to accurately define and classify direct and indirect CSCs, the research adopts two different approaches: To define and classify indirect CSCs, the research adopted the "External Damage Approach Resulting from the Economic Activities of Companies." To define and classify direct CSCs, the research adopted the "Supporting Social Responsibilities Approach. "The characteristics of direct CSCs can be inferred by studying the nature of the obligation to incur these costs, the role they play, the impact they have, the justifications that justify them, the benefits they achieve, and the beneficiaries. Through the characteristics of direct CSCs, the criteria for distinguishing between CSCs and CECs can be determined. Findings: This research is not merely about finding a new, more specific definition related to CSC and CEC, but has been able to establish a set of criteria to distinguish between CSC and CEC. Novelty/Value: Because there aren't many publications in this area, this research is regarded as a contribution to the field of CSR accounting theory.  The results of this research will improve businesses' capacity to truthfully report on their social performance.  In terms of education, this research will clear up any confusion students might have on what CSCs mean.